(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. The question of age-related cataract treatment effectiveness is one of the most important in ophthalmology. This question becomes particularly topical if this disease is progressed together with glaucomatous process. Purpose. To study the condition of glutathione system of animals eye lens with experimental ocular hypertension while modeling age-related cataract with the help of light illumination. Methods. Experimental studies were carried out on 39 rabbits, which were divided into three groups: in first group (9 animals) the light cataract was modeled, in the second group (8 animals) ocular hypertension was modeled, and in third one (10 animals) the ocular hypertension was induced after light illumination. Control group comprised 12 animals. In eye lenses and chamber liquid of experimental animals, the levels of reduced and oxidized glutathione were detected. Results. After general estimation of this study results it can be stated, that under the influence of cataractogenic factor, light energy, more sharp drop of restorative potential of glutathione in eye lenses was indicated in conditions of ocular hypertension as compared with studies, in which the light illumination was influenced in conditions of normal intraocular tension. Conclusion. It was indicated that modeling of light cataract in conditions of ocular hypertension causes more sharp injure of eye lens glutathione system as compared with cataractogenic influence of just light energy. The data on the high level of glutathione restorative potential reduction discovered an important link of cataractogenic influence of ocular hypertension and gives ground to consider it to be a risk factor of cataract progression